1998
DOI: 10.1002/(sici)1096-9861(19981102)400:4<571::aid-cne9>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Innervation of the medial rectus muscle in the ratfish,Hydrolagus colliei

Abstract: Oculomotor organization in elasmobranch fish (sharks, skates, and rays) differs from that in other vertebrates in that the medial rectus muscle is innervated by contralateral rather than ipsilateral motoneurons. Distinguishing whether this innervation pattern is unique to the elasmobranchs, or is the ancestral pattern for cartilaginous fishes, requires examination of a representative of the sister group to the elasmobranchs, the holocephalans (ratfish). In the present study, the innervation pattern of the medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Likewise, we can assume that a counteraction occurs between SR/IR whereas the counteraction should be between the NR/LR. The detail of this connection remains to be determined in chondrichthyans and lungfish [11][12][13].…”
Section: Elasmobranchs and Lungfish May Have A Unique Connection Of T...mentioning
confidence: 98%
See 4 more Smart Citations
“…Likewise, we can assume that a counteraction occurs between SR/IR whereas the counteraction should be between the NR/LR. The detail of this connection remains to be determined in chondrichthyans and lungfish [11][12][13].…”
Section: Elasmobranchs and Lungfish May Have A Unique Connection Of T...mentioning
confidence: 98%
“…Among teleosts, frogs, birds, and mammals each have a specific pattern of innervation by vestibular inputs [1,4,17,42,45]. By contrast, studies in chondrichthyans (cartilaginous fishes) revealed a different pattern with a combination of ipsilateral and contralateral nerve fibers [11,12]. Many details of vestibular relationships are incomplete in lampreys (which lack a horizontal canal) but can be compared to the pattern of connections in gnathostomes [42,43,[46][47][48].…”
Section: Vestibular Inputs To the Motor Neurons Which Innervate The E...mentioning
confidence: 99%
See 3 more Smart Citations